Analisis Anestesi Perioperatif - Aurelia Shira Jelita; Elvina Fabiola; Kiran Dhevy Hari Huma; Mahima Farhanah Madsyal; Liss Dyah Dwi A (STIKes Ibnu Sina Ajibarang, 2024)
Perioperative anesthesia management is divided into preoperative preparation, intraoperative services (during the operation), and postoperative services. Preoperative anesthetic management is the first step in a series of anesthetic procedures carried out on patients who are planned to undergo surgery. Intraoperative anesthesia management is carried out by pre-induction, induction and maintenance assessments. Postoperative anesthetic management consists of discontinuing the anesthetic drug and stabilizing the patient.